2003
DOI: 10.1007/s00108-003-0862-3
|View full text |Cite
|
Sign up to set email alerts
|

52-jähriger Patient mit subkutaner Raumforderung unter Immunsuppression

Abstract: We report the case of a 52-years-old male patient, who was diagnosed with subcutaneous alveolar echinococcosis 6 months after liver transplantation for HCV-related cirrhosis. Nether the explanted nor the transplantated liver revealed an echinococcus focus. Therefore a rare primary extrahepatic manifestation was likely. Interestingly, the echinococcal larvae had developed protoscolices. The development of mature tapeworms in human is a rarity, which could be related to the immunosuppressive therapy after liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Kolligs et al (2003) reported the case of a patient with subcutaneous alveolar echinococcosis 6 months after liver transplantation for HCV-related cirrhosis. Neither the explanted nor the transplantated liver revealed an echinococcus focus.…”
Section: A 1bmentioning
confidence: 99%
“…Kolligs et al (2003) reported the case of a patient with subcutaneous alveolar echinococcosis 6 months after liver transplantation for HCV-related cirrhosis. Neither the explanted nor the transplantated liver revealed an echinococcus focus.…”
Section: A 1bmentioning
confidence: 99%
“…Liver is the most common organ involved (45-75%), followed by the lung (10-50%) [4]. The disease usually metastasizes to spleen, retroperitoneum, brain, bone, pancreas [5], and adrenal glands [6].…”
Section: Introductionmentioning
confidence: 99%